Grazing evaluation of three subtropical grasses and the native grassland in the region of Campos Gerais, Parana, Brazil - Postiglioni, Sérgio Roberto; Picanço, Roberto Guilherme Cavagnari (Pesquisa Agropecuaria Brasileira, 2014)
Three kinds of subtropical grasses and the native grassland were evaluated with grazing animals in the former Unit of the Empresa Brasileira de Pesquisa Agropecuária (EMBRAPA), at Ponta Grossa, State of Parana, Brazil, intending to its application in finishing beef cattle in this region. The treatments were factor combinations of the four types of pastures with two levels of Nitrogen fertilizer. The subtropical grasses were Cynodon plectostachyus (African stargrass), Paspalum notatum, cv IPEAME (Bahia grass) and Paspalum notatum, cv Tifhi Bahia. Nitrogen fertilizer levels were 30 and 60 kg/N/ha/year. Experimental design was randomblocks with three replications. To provide a total check treatment, one half of the native grassland plots have not received any one source of fertilizer, instead of the 30 kg/N/ha. The stocking rate was adjusted through the put-and-take system, with a minimum of three testers by experimental unit. The animals were introduced into the plots at fifteen months age. The results, at an average of three years, have demonstrated remarkable advantage of the subtropical grasses over the native grassland. In terms of live weight gains per ha/year, the differences among the results produced by the three grasses were not significant: 190, 204 and 211 kg/ha/year, respectively for the African stargrass, Paspalum IPEAME and Tifhi Bahia. Only the African stargrass has presented response to the second level of 60 kg/N/ha/year. The animals supported on the cultivated grasses have attained slaughter conditions, with an average of 466 kg, at three-year age, while those supported on the native grassland have attained just 340 kg in this same period.